PERANAN GEREJA DAN HAM TERHADAP KAUM LGBT DALAM RANGKA MEMANUSIAKAN-MANUSIA - Endang Pasaribu; Vanny Miracleson Waruwu; Ezra Siorasi (STT BIBLIKA JAKARTA, 2023)
The purpose of this research is to find out whether the church as a divine institution based on 'Love' is able to become a forum for LGBT people and become a bridge to humanize humans. The research used in this article is a qualitative method with a postpositivism philosophy. This method is used for social research, humanities and theology. The objects of research are the church, LGBT and human rights. The results of this study the authors found several church policies related to LGBT and human rights. One of the policies related to LGBT is to become a born again human being, namely repentance. Then for those who have repented, there is coaching, so that LGBT people are able to manifest themselves in the church community and social society.